Palynology of the Barail (Oligocene) and Surma (Lower Miocene) sediments exposed along Sonapur-Badarpur Road Section, Jaintia Hills (Meghalaya) and Cachar (Assam). Part-VII. Discussion - Singh, H.P.; Rao, M.R.; Saxena, R.K. (Journal of Palaeosciences, 1986)
The palynofloral assemblages from the Barail (Oligocene) and Surma (Lower Miocene) sediments exposed along Sonapur-Badarpur Road Section, Meghalaya and Assam have been discussed and interpreted. The total assemblage consists of 68 genera and 113 species. Qualitative analysis of the assemblage reveals that Lycopodiaceae, Polypodiaceae, Matoniaceae, Hymenophyllaceae, Ophioglossaceae, Schizaeaceae, Cyatheaceae, Osmundaceae, Gleicheniaceae, Parkeriaceae, Podocarpaceae, Pinaceae, Palmae, Potamogetonaceae, Araceae, Oleaceae, Bombacaceae, Labiatae, Mimosaceae and Malvaceae are represented in the assemblage. The present day distribution of these families indicates the prevalence of mainly tropical-subtropical climate during the deposition of Barail-Surma sediments. The environment of deposition has been interpreted as a coastal marine. Quantitatively, the pteridophytic spores constitute a major part (62%) of the assemblage followed by gymnospermous pollen grains (23%), angiospermous pollen grains (5.5%), dinoflagellate cysts (5%) and fungal remains (4.5%). A comparison of this assemblage with similar Oligocene-Lower Miocene assemblages of India has been made. The age of the sediments has also been discussed.